Youth sport: Friend or Foe?. Issue 1 (February 2019) - McKay, Carly D.; Cumming, Sean P.; Blake, Tracy
Abstract: Participation in youth sport has been promoted as part of a healthy lifestyle, with benefits for physical fitness, social development, and mental wellbeing. Yet, sport carries an inherent risk of injury, which for young athletes may have both immediate and long-term consequences. Amidst significant public debate about the pros and cons of youth sport, this review considers the physiological, psychological, and social factors that inform decisions around youth sport participation. With particular emphasis on growth and maturation, early sport specialization, and injury prevention, it highlights the unique features of the youth sport environment that can influence lifelong musculoskeletal health and physical activity behaviour. Though there have been few robust, longitudinal studies, current evidence suggests that sport has positive effects on child and adolescent wellbeing when maturity status and training load are managed appropriately.